BRIGHT AND THE BULLY PICTURE BOOK DESIGN AS A RESPONSE TO THE PHENOMENA OF BULLYING IN CHILDREN (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2021)
Schools are actually places where the teaching and learning process takes place as well as a place for the growth and development of a person. Comfort in studying at school is an important factor to support an effective learning process, but in today's modern era schools are often a place for students to bully. We can prevent bullying by raising awareness in children about the dangers of bullying. This awareness raising can be started from providing understanding related to bullying and cultivating moral values. In an effort to achieve this goal, an appropriate media is needed to convey information related to intimidation. Through the science of visual communication design, the author provides an alternative means of conveying knowledge related to bullying through stories conveyed in the form of picture books written by Tramaine William in response to the phenomenon of bullying in children. The work was designed in the study project